PILIHAN BAHASA PADA MASYARAKAT SUKU JAWA DI DAERAH TRANSMIGRAN KECAMATAN KURANJI TANAH BUMBU (THE CHOICE OF LANGUAGE IN JAVANESE COMMUNITIES IN THE TRANSMIGRANT AREA OF KURANJI TANAH BUMBU SUB-DISTRICT) - Salamah, Ummie (JURNAL BAHASA, SASTRA, DAN PEMBELAJARANNYA, 2024)
AbstractThe Choice of Language in Javanese Communities in the Transmigrant Area of Kuranji Tanah Bumbu Sub-District. This study aims to understand the choice of language by the Javanese in the realm of family, community, work/government, education, and transactions. Types of quantitative and qualitative research approaches. The research data is the response of the Javanese population of Kuranji District. The results showed that the use of SBD was more widely used in the family domain with a proportion of 75%, in the community and transaction domains, the use of SBD, namely more frequent use of SBD from BI with a proportion of 39% in the community domain, 45%, in the transaction domain. Then in the realm of work/government and the realm of education, the use of BI is more widely used with the proportion of 86% and 97%.Keywords: Choice of Language, Javanese Ethnic Community, Domain, Multilingual, Kuranji DistrictAbstrakPilihan Bahasa pada Masyarakat Jawa di Daerah Transmigran Kecamatan Kuranji Tanah Bumbu. Penelitian ini bertujuan memahami pilihan bahasa oleh penduduk suku Jawa pada ranah keluarga, masyarakat, pekerjaan/pemerintahan, pendidikan, dan transaksi. Jenis pendekatan penelitian kuantitatif dan kualitatif. Data penelitian adalah respon penduduk suku Jawa Kecamatan Kuranji. Hasil penelitian diperoleh penggunaan SBD lebih banyak digunakan pada ranah keluarga dengan persentase 75%, pada ranah masyarakat dan transaksi, penggunaan SBD yaitu lebih sering menggunakan SBD dari BI dengan persentase 39% pada ranah masyarakat  45%, pada ranah transaksi. Kemudian pada ranah pekerjaan/pemerintahan dan ranah pendidikan, penggunakan BI lebih banyak digunakan dengan persentase 86% dan 97%.Kata Kunci: Pilihan Bahasa, Masyarakat Suku Jawa, Ranah, Multilingual, Kecamatan Kuranji